If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying k + -1 = -15 Reorder the terms: -1 + k = -15 Solving -1 + k = -15 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + k = -15 + 1 Combine like terms: -1 + 1 = 0 0 + k = -15 + 1 k = -15 + 1 Combine like terms: -15 + 1 = -14 k = -14 Simplifying k = -14
| r-3=-21 | | 4x+7=-3+2x+22 | | 4n-6=6n-7-5 | | n(n+4)+28=28(n-1)(n-8) | | x^3-9x^2-10x= | | -13=n+(-11) | | -3x+7=-7-x | | n(n+4)+28=(n-1)x(n+8) | | x^2+15x-98=0 | | 9+r=-3 | | 25f^2-64=0 | | 16+8=2(8p+4) | | 15j+2=-28 | | 7(x+23)=5x+25-5+2x | | y=x^2+7x+1 | | -8+7k+k=-k+7k | | n-18=1 | | -201(4x-1)=-15 | | m-9=-24 | | u^2-2u+10= | | v^2-8v-5=4 | | -12=5+x | | 4x+10=7x-5 | | ln(5+x)=1 | | 1=ln(5+x) | | -7q=-49 | | 3p+6=-4+p | | 0=x+(-10) | | v-16=-29 | | n+17=29 | | 4(t-2)+t-2= | | -10=7x+4+7x |